2018
DOI: 10.1186/s12889-018-5555-x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of transfusion-transmissible infections (HBV, HCV, syphilis and HIV) among prospective blood donors in a tertiary health care facility in Calabar, Nigeria; an eleven years evaluation

Abstract: BackgroundProvision of constant and safe blood has been a public health challenge in Sub-Saharan Africa with high prevalence of transfusion-transmissible infections (TTIs). This study was aimed at determining the trend and seroprevalence of HBV, HCV, syphilis and HIV across the years within study among prospective blood donors at blood bank in University of Calabar Teaching Hospital (UCTH), Calabar, Nigeria.MethodsA retrospective analysis of blood donor data from January 2005 to December 2016 was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 25 publications
11
80
11
1
Order By: Relevance
“…The finding was comparable with studies done in Ethiopian and sub-Saharan Africa [14][15][16] and this might be due to knowledge and attitude difference between the two sex, due to physiologic difference (menstruation cycle and birth related issues) that, females were less participate in voluntary blood donation. Despite the fact that males were more in the donor pool of this study, females were comparatively high when compared with female involvement in blood donation in other studies in Ethiopia and Nigeria [17,18]. This might be due to the fact that the present study comprised of voluntary donors while the other Ethiopian and Nigerian studies comprised of voluntary, replacement and commercial donors.…”
Section: Discussionmentioning
confidence: 55%
“…The finding was comparable with studies done in Ethiopian and sub-Saharan Africa [14][15][16] and this might be due to knowledge and attitude difference between the two sex, due to physiologic difference (menstruation cycle and birth related issues) that, females were less participate in voluntary blood donation. Despite the fact that males were more in the donor pool of this study, females were comparatively high when compared with female involvement in blood donation in other studies in Ethiopia and Nigeria [17,18]. This might be due to the fact that the present study comprised of voluntary donors while the other Ethiopian and Nigerian studies comprised of voluntary, replacement and commercial donors.…”
Section: Discussionmentioning
confidence: 55%
“…2% and 0.7% donors were tested positive for HBV and HCV respectively. Henshaw Uchechi Okoroiwu et al, [11] conducted a study in a total of 24,979 prospective donors over a period of 12 years from 2005 to 2016 and found that 3739 units (14.96%) were positive for at least one infective agent. 4.1% and 3.6% donors were positive for HBV and HCV respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prospectively screened donors from 2005 to 2016 in Nigeria showed 14. 96% were infected with at least one of the four TTI with overall prevalence of HBV, HCV, Syphilis, and HIV of 4.1, 3.6, 3.1, and 4.2%, respectively [24]. However, the rate of all TTI declined significantly over the years with a remarkable decline in HIV.…”
Section: Africamentioning
confidence: 99%